Determining Urban and Rural Perceptions of Forest Ecosystem Services - Baykalı, Beyzanur; Şen, Gökhan (Bartin Orman Fakultesi Dergisi, 2024)
To ensure the sustainability of forest ecosystem products and services, changing people’s perspectives and increasing their awareness of these resources and services is crucial. Determining people’s perceptions and opinions regarding ecosystem services is critical to this context. This study aims to assess the knowledge levels and views of individuals living in both urban and rural areas of Kastamonu province in Turkey regarding forests and the ecosystem services they provide. Data for the research were collected through 97 face-to-face surveys conducted in urban and rural settings. Differences in participants’ opinions based on their place of residence were analyzed using Kruskal-Wallis and Mann-Whitney U tests. The study results reveal that when people think of forests, the top three associations in terms of importance are nature and wildlife (41.8%), clean air (15.5%), and wild food (7.6%). Regarding the importance of forest ecosystem services, the ranking is as follows: regulatory services (39.2%), supporting services (28.2%), provisioning services (25.1%), and cultural services (7.5%). To ensure the sustainable use and continuity of forest ecosystem services, voluntary payment tendencies per capita are approximately 846 TL/person for the general population, 413.8 TL/person (24,8 $) for rural residents, and 1443.3 TL/person (86,4 $) for urban dwellers in Kastamonu. The total voluntary payment tendency for Kastamonu amounts to 318414942 TL (19066762 $).
Keywords: Economics and Law; Ormancılık Politikası; Ekonomisi ve Hukuku; Forestry Politics; 11. Sustainability; 15. Life on land; 12. Responsible consumption